Factors associated with a high level of unmet needs and their prevalence in the breast cancer survivors 1–5 years after post local treatment and (neo)adjuvant chemotherapy during the COVID-19: A cross-sectional study - Miroševič, Špela; Prins, Judith; Borštnar, Simona; Besić, Nikola; Homar, Vesna; Selič-Zupančič, Polona; Smrdel, Andreja Cirila Škufca; Klemenc-Ketiš, Zalika (Frontiers in Psychology, 2022)
Objective: To assess the prevalence of unmet needs in post-treatment breast cancer survivors and identify sociodemographic, clinical, and psychosocial variables associated with reported unmet needs during the Covid-19 pandemic. Materials and methods: In this cross-sectional study, 430 post-treatment breast cancer survivors, ranging between 1–5-years after the procedure, completed the Cancer Survivors' Unmet Needs (CaSUN) questionnaire from September 2021 and January 2022. The multivariate logistic analysis identified factors associated with at least one reported unmet need in the total CaSUN scale and specific domains. Results: 67 percent of survivors reported at least one unmet need. The most frequently reported unmet needs were the lack of accessible hospital parking (43%) and recurrence concerns (39.5%). The majority of reported unmet needs relate to comprehensive care (44%), followed by the psychological and emotional support domain (35.3%). Younger age (OR = 0.95, 95% Cl = 0.92-0.99; p < 0.001), three or more comorbidities (OR = 0.27, 95% Cl = 0.11-0.71, p < 0.01), a lower quality of life (OR = 0.06, 95% Cl = 0.01-0.47, p < 0.01) and low resilience (OR = 0.95, 95% Cl = 0.93-0.99) were associated with a high level of unmet needs in the multivariate regression model. Results are presented for factors associated with a high level of unmet needs for comprehensive cancer care and psychological and emotional support domain. Conclusions: A high prevalence found in our study could be attributed to the COVID-19 pandemic, where patients may have missed adequate follow-up care, although comparing to studies done in non-pandemic time is difficult. Family physicians should be more attentive toward younger cancer survivors and those with more comorbidities as both characteristics can be easily recognised in the family practice.